THE EXPOSURE EFFECT OF WATER PIPE SMOKE (WPS) ON THE RESPIRATORY TRACT OF SWISS MICE - Al-Easawi, Nada (Iraqi Journal of Science, 2024)
One of the most common means of smoking tobacco is Water Pipe (WP); it’s called (Arghile or Narghile) in the Middle East countries. It represents one of the causes of indoor air pollution. During the last few year’s this method of smoking spread among the young Iraqies. Some of the previous studies confirmed that WP smoking has a negative health effects more than those of Cigarettes smoking.In this research study , mice were exposed to water pipe smoke using a special inhalation glass chamber (whole body exposure).This smoke consist of a respirable particulate matter in which are (less than 2.5μm ) in diameter . Mice exposed daily to 100 puffs of WP smoke on the bases of (1hr exposure per day), the exposure experiment continued daily for the periods of 3, 5, 7 weeks consequently.The results indicated a remarkable reduction in bronchioles diameters and an obvious increase in alveoli diameter, while the histological examination showed different degrees of hyperplasia on the epithelial layer, thickening of the parenchyma tissue and the infiltration of inflammatory cells.The research concluded that intensity of the observed symptoms depended on the length of exposure periods, the highest levels of effects represented by the group of 7 weeks exposure in which was the longest period. The previous mentioned group suffered from hyperplasia and increased secretion of mucus leads to early signs of chronic bronchiolitis.